# Proof

### Proof of Linearity Rules

It follows from the definition of Riemann integrable functions that they are bounded. By applying the rules of adding Riemann upper and lower integrals of bounded functions we get the of inequations $\int_{a~*}^{b}f(x)dx + \int_{a~*}^{b}g(x)dx \le \int_{a~*}^{b}(f+g)(x)dx \le \int_{a}^{b~*}(f+g)(x)dx \le \int_{a}^{b~*}f(x)dx + \int_{a}^{b~*}g(x)dx.$ Because, by hypothesis $\int_{a~*}^{b}f(x)dx =\int_{a}^{b~*}f(x)dx = \int_{a}^{b}f(x)dx\quad\quad\text{and}\quad\quad\int_{a~*}^{b}g(x)dx =\int_{a}^{b~*}g(x)dx = \int_{a}^{b}g(x)dx$ we get the result that the function $$f+g:[a,b]\mapsto\mathbb R$$ is Riemann integrable and that $\int_{a~*}^{b}(f+g)(x)dx = \int_{a}^{b~*}(f+g)(x)dx = \int_{a}^{b}(f+g)(x)dx=\int_{a}^{b}f(x)dx+\int_{a}^{b}g(x)dx.$ Similarly, by applying the rules of scalar multiplication of Riemann upper and lower integrals, we get the equation chain $\int_a^{b~*}(\lambda\cdot f)(x)dx=\lambda\cdot\int_a^{b~*}f(x)dx =\lambda\cdot\int_a^{b}f(x)dx=\lambda\cdot\int_{a~*}^{b}f(x)dx=\int_{a~*}^{b}(\lambda\cdot f)(x)dx.$ This means that the function $$\lambda\cdot f:[a,b]\mapsto\mathbb R$$ is Riemann integrable and that $\int_a^{b}(\lambda\cdot f)(x)dx =\lambda\cdot\int_a^{b}f(x)dx.$

### Proof of Monotony

If $$f(x)\le g(x)$$ for all $$x\in[a,b]$$, then we have $$f(x)-g(x)\le 0$$ for all $$x\in[a,b]$$. It follows from the linearity rules that

$\int_a^{b}(f-g)(x)dx=\int_a^{b}f(x)dx-\int_a^{b}g(x)dx\ge \int_a^{b}0dx=0.$ It follows $\int_a^{b}f(x)dx\le\int_a^{b}g(x)dx.$

Thank you to the contributors under CC BY-SA 4.0!

Github:

### References

#### Bibliography

1. Forster Otto: "Analysis 1, Differential- und Integralrechnung einer VerĂ¤nderlichen", Vieweg Studium, 1983